2014
DOI: 10.4103/0970-9185.142842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computer-integrated patient-controlled epidural analgesia with no initial basal infusion versus moderate basal infusion for labor and delivery : A randomized controlled trial

Abstract: Background and Aims:Computer-integrated patient-controlled epidural analgesia (CIPCEA) is a novel epidural drug delivery system. It automatically adjusts the basal infusion based on the individual's need for analgesia as labor progresses.Materials and Methods:This study compared the time-weighted local anesthetic (LA) consumption by comparing parturients using CIPCEA with no initial basal infusion (CIPCEA0) with CIPCEA with initial moderate basal infusion of 5 ml/H (CIPCEA5). We recruited 76 subjects after eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Many previous studies of PCA using the VFIM were conducted in patients using “computer-integrated” patient-controlled epidural analgesia (PCEA) during labor and delivery [ 14 , 15 , 16 , 17 ]. Their results suggested that patient satisfaction was greater in those using the computer-integrated PCEA than in those using traditional PCEA, but that the incidence of breakthrough pain and the cumulative local anesthetic consumption did not differ significantly between groups [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies of PCA using the VFIM were conducted in patients using “computer-integrated” patient-controlled epidural analgesia (PCEA) during labor and delivery [ 14 , 15 , 16 , 17 ]. Their results suggested that patient satisfaction was greater in those using the computer-integrated PCEA than in those using traditional PCEA, but that the incidence of breakthrough pain and the cumulative local anesthetic consumption did not differ significantly between groups [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural anesthesia and analgesia are commonly used for obstetric anesthesia. Epidural anesthesia is safe for use in cesarean sections, even in patients with cardiac diseases and severe pulmonary hypertension [4,7,[10][11][12][13][14][15][16]. Several methods, including wound infiltration with a local anesthetic and magnesium sulphate, wound infiltration with tramadol and levobupivacaine, a magnesium sulphate infusion for preemptive analgesia, a transverse abdominal plane block (TAPB) performed by adding dexamethasone to levobupivacaine, infiltration by placing a continuous catheter for a TAPB or the wound area, the administration of intrathecal and intravenous betamethasone, and the addition of dexmedetomidine to increase the efficacy of epidural anesthesia and analgesia have all been used to treat pain after a cesarean section [17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In some previous studies, higher volumes of epidural analgesia provided better pain scores when compared to lower volumes [8,9]. Conversely, some studies showed that the delivery of small volumes (5 mL) via the epidural route was also sufficient [7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many previous studies of PCA using the VFIM were conducted in patients using "computer-integrated" patient-controlled epidural analgesia (PCEA) during labor and delivery [13][14][15][16]. Their results suggested that patient satisfaction was greater in those using the computer-integrated PCEA than in those using traditional PCEA, but that the incidence of breakthrough pain and the cumulative local anesthetic consumption did not differ statistically significantly between groups [14,16].…”
Section: Discussionmentioning
confidence: 99%